Global warming : [videorecording (DVD)] : what's up with the weather? - Palfreman, Jon (WGBH Boston Video, 2007)
One of today's hottest topics is global warming. Will the earth's temperature rise nearly 10 degrees, wreaking havoc on the ice caps? Or will the weather stay normal. A heated debate between scientists, climatologists, and futurists.